The Effects of an Enhancing Health Literacy Program with Family Participation on Health Literacy of Caregivers, Fall Prevention Behaviours, and Balance of Older Adults at Risk for Fall - Tiparat, Wararat; Rodniam, Jaroonrat; Suwanweala, Perawit (Princess of Naradhiwas University Journal, 2022)
This quasi-experimental research, two-group pre-posttest design, aimed to study 1) the health literacy regarding fall prevention of older adults among caregivers, and 2) fall prevention behaviours and balance of older adults at risk for fall. Sample was 34 older adults at risk for fall and their caregivers. The experimental group received an enhancing health literacy program with family participation for 8 weeks, while the control group received routine nursing care. Data were collected using a questionnaire regarding health literacy, and fall prevention behaviours, as well as fall assessment tool (The Berg Balance Scale: BBS). The research tools were validated by three experts. The questionnaire of health literacy, fall prevention behaviours, and the BBS were tested using Cronbach's alpha coefficient, yielding values of, 0.83, 0.82, and 0.78, respectively. Reliability of the questionnaire regarding the health literacy in the knowledge part was verified using KR-20, obtaining a value of 0.77. Data were analyzed by mean, standard deviation, Dependent t-test, and Independent t-test. The results indicated that after receiving the enhancing health literacy program with family participation, the experimental group had a higher mean score of the caregivers’ health literacy, as well as the prevention behaviours and balance of the older adults at risk for fall than before receiving the program with statistical significance (p<.05), and the experimental group had higher mean score of the caregivers’ health literacy, as well as the prevention behaviours and balance of the older adults at risk for fall higher than the control group with statistical significance (p<.05). The findings from this study can be used as a guideline for enhancing health literacy with family participation to prevent fall, and to promote balance in older adults.